2004
DOI: 10.1099/ijs.0.02857-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium degerlachei sp. nov., Flavobacterium frigoris sp. nov. and Flavobacterium micromati sp. nov., novel psychrophilic bacteria isolated from microbial mats in Antarctic lakes

Abstract: Taxonomic studies were performed on 36 strains that were isolated from microbial mats in Antarctic lakes of the Vestfold Hills, the Larsemann Hills and the McMurdo Dry Valleys. Phylogenetic analysis based on 16S rRNA gene sequences indicated that these strains are related to members of the genus Flavobacterium; sequence similarity values with their nearest phylogenetic neighbours ranged from 96·8 to 98·5 %. Results of DNA–DNA hybridization and comparison of repetitive extragenic palindromic DNA-PCR fingerprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 24 publications
(29 reference statements)
4
54
0
Order By: Relevance
“…Flavobacterium species are physiologically diverse: they can be psychrophilic, psychrotolerant or mesophilic, and can be halophilic, halotolerant or sensitive to salts. As a reflection of their physiological diversity, Flavobacterium species have been isolated from various habitats such as freshwater sediments and soil (Bernardet et al, 1996;Tamaki et al, 2003;McCammon & Bowman, 2000), a glacier (Zhu et al, 2003) and Antarctic lakes (Van Trappen et al, 2003, 2004McCammon et al, 1998;McCammon & Bowman, 2000;Humphry et al, 2001;Yi et al, 2005).…”
mentioning
confidence: 99%
“…Flavobacterium species are physiologically diverse: they can be psychrophilic, psychrotolerant or mesophilic, and can be halophilic, halotolerant or sensitive to salts. As a reflection of their physiological diversity, Flavobacterium species have been isolated from various habitats such as freshwater sediments and soil (Bernardet et al, 1996;Tamaki et al, 2003;McCammon & Bowman, 2000), a glacier (Zhu et al, 2003) and Antarctic lakes (Van Trappen et al, 2003, 2004McCammon et al, 1998;McCammon & Bowman, 2000;Humphry et al, 2001;Yi et al, 2005).…”
mentioning
confidence: 99%
“…Members of the phylum Bacteroidetes are abundant in freshwater and marine ecosystems and these bacteria may have a specialized role in the uptake and degradation of organic matter in cold, aquatic environments (Kirchman, 2002). Several novel species, added to the genus Flavobacterium since 1996, have originated from Antarctic habitats (Van Trappen et al, 2003, 2004; and references cited therein).…”
mentioning
confidence: 99%
“…Members of the phylum Bacteroidetes are abundant in freshwater and marine ecosystems and these bacteria may have a specialized role in the uptake and degradation of organic matter in cold, aquatic environments (Kirchman, 2002). Several novel species, added to the genus Flavobacterium since 1996, have originated from Antarctic habitats (Van Trappen et al, 2003, 2004; and references cited therein).During the MICROMAT project (November 1998-February 2001, 746 bacterial strains were isolated under heterotrophic conditions from microbial mat samples that were collected from ten Antarctic lakes (Van Trappen et al, 2002). Numerical analysis of the fatty acid composition of the isolates and 16S rRNA gene sequence analysis, performed on representative strains, showed that the diversity of heterotrophic bacteria in microbial mats from Antarctic lakes is very high.…”
mentioning
confidence: 99%
See 2 more Smart Citations